Andrographolide-Loaded Ethosomal Gel for Transdermal Application: Formulation and In Vitro Penetration Study - Nooryza Martihandini; Silvia Surini; Anton Bahtiar (Tabriz University of Medical Sciences, 2022)
Background: Andrographolide is a phytoconstituent with anti-inflammatory activity, however, the compound's poor oral bioavailability has hindered its effective formulation for oral administration. This study, therefore, aims to develop an ethosome for improving andrographolide penetration through the transdermal delivery system. Methods: This study developed 3 ethosome formulas with different andrographolide-phospholipid weight ratios (1:8, 1:9 and 1:10), using the thin-layer dispersion-sonication method. Subsequently, the ethosomes were evaluated for particle size, polydispersity index, zeta potential, morphology, as well as entrapment efficiency, and incorporated into a gel dosage form. Subsequently, an in vitro penetration study was performed using Franz diffusion cells for 24 hours and the stability of the gels at 5 ± 2°C, 30 ± 2°C, and 40 ± 2°C, were studied for 3 months. Results: The results showed the optimal formula was E2, a 1:9 weight ratio formula of andrographolide and phospholipid. Based on the transmission electron micrograph, E2 possessed unilamellar, as well as spherical-shaped vesicles, and exhibited superior characteristics for transdermal delivery, with a particle size of 89.95 ± 0.75 nm, polydispersity index of 0.254 ± 0.020, a zeta potential of -39.3 ± 0.82 mV, and entrapment efficiency of 97.89 ± 0.02%. Furthermore, the cumulative andrographolide penetration and transdermal flux for the ethosomal gel of E2 (EG2) were 129.25 ± 4.66 µg/cm2 and 5.16 ± 0.10 µg/cm2 /hours, respectively. All the ethosomal gel formulations exhibited improved penetration enhancement of andrographolide, compared to the nonethosomal formulations. Also, the andrographolide levels in the ethosomal and nonethosomal gels after 3 months ranged from 98.13 to 104.19%, 97.93 to 104.01%, and 97.23 to 102.26% at storage temperatures of 5 ± 2°C, 30 ± 2°C/RH 65% ± 5%, and 40 ± 2°C/RH 75% ± 5%, respectively. Conclusion: This study concluded that encapsulation into ethosome enhances andrographolide delivery through the skin.